Cytocompatibility and antibacterial activity of nanostructured H2Ti5O11·H2O outlayered Zn-doped TiO2 coatings on Ti for percutaneous implants. Issue 1 (December 2017) - Zhang, Lan; Zhang, Juan; Dai, Fang; Han, Yong
Abstract To improve skin-integration and antibacterial activity of percutaneous implants, the coatings comprising an outer layer of H2 Ti5 O11 ·H2 O (HTO) nanoarrays and an inner layer of microporous Zn-doped TiO2 were fabricated on Ti by micro-arc oxidation (MAO) followed with hydrothermal treatment (HT). During HT process, a large proportion of Zn2+ migrated out from TiO2 layer. TiO2 reacted with OH− and H2 O, resulting in the nucleation of HTO. The nuclei grew to nanoplates, nanorods and nanofibres with HT process prolonged. Simultaneously, the orientation of nanoarrays changed from quasi-vertical to parallel to substrate. Compared to Ti, adhesion and proliferation of fibroblasts were enhanced on as-MAOed TiO2 and HTed coatings. The phenotype, differentiation and extracellular collagen secretion were obviously accelerated on vertical nanorods with proper interspace (e.g. 63 nm). HTed coatings showed enhanced antibacterial activity, which should be ascribed to the nano-topography of HTO.